Assessing customer satisfaction on service quality of Light Rail Transit (LRT) transportation in Malaysia - Azlan N.N.I.M.; Norhisham S.; Roslan R.; Yuzainee M.Y.; Bakar M.F.A.; Ismail N.; Rais N.M.; Yukawa S.; Wakijan A.; Masjuki S.A. (American Institute of Physics, 2025)
The public transportation system is a crucial component of core infrastructure and plays a significant role in the country's growth. Rail transportation is the preferred mode of travel for many users due to its dedicated railway lines, distinguishing it from other forms of public transportation that share the road with other vehicles. However, in Malaysia, there is a lack of safety and security at Light Rail Transit (LRT) stations, which has resulted in accidents involving passengers falling onto the tracks. Such incidents can erode customers' trust in the quality of LRT service. Therefore, this research aims to evaluate customer satisfaction with the service quality of LRT in Malaysia. The data for this study were collected through survey questionnaires from 139 respondents who use the LRT as their daily mode of transportation. These data were then categorized into seven dimensions of service quality: assurance, empathy, reliability, responsiveness, tangibility, safety and security, and accessibility. Importance-Performance Analysis (IPA) was used to analyze the data. The research findings revealed that the most critical and top-priority dimension of LRT service is accessibility, as it falls within the first quadrant of the IPA matrix. Based on these results, LRT operators and stakeholders can focus on improving customer satisfaction by addressing the various dimensions accordingly. Overall, this study highlights the importance of evaluating customer satisfaction with LRT service quality and provides insights that can be utilized to enhance the overall customer experience. ? 2024 Author(s).